A Strategic Framework for Local Wisdom-Based Tourism and Creative Economy Development to Support Sustainable Regional Growth: Evidence from Kuningan Regency - Saefullah, Aep; Sukardi; Salima, Rianti (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to formulate a sustainable development strategy for tourism and the creative economy based on local wisdom in Kuningan Regency. The region has significant potential supported by natural resources and cultural diversity; however, its development remains constrained by limited funding, low innovation capacity, and suboptimal community participation. This research employs a descriptive qualitative approach using data triangulation techniques, including in-depth interviews, focus group discussions (FGDs), observation, and document analysis. Data were analyzed through thematic coding with the assistance of NVivo software. The findings identify four key strategic factors: (1) the integration of local wisdom into tourism products, (2) multi-stakeholder collaboration, (3) the utilization of digital technology, and (4) community-based environmental conservation. These factors collectively shape a holistic and adaptive development model that strengthens regional competitiveness while ensuring sustainability. This study contributes by providing a context-based strategic framework that can be applied to similar regions seeking to develop tourism and creative economy sectors in a sustainable and inclusive manner.